Innovation in the Teaching-learning Processes: A Case Study Using Just-in-Time Teaching and Peer Instruction - Maldonado-Fuentes, Ana Carolina (2016)
Learning quality constitutes one of the main challenges faced by Higher Education, thus a student centered teaching and the development of educational innovations that use active methodologies have been promoted. This article aims to evaluate the impact of using Just-in-Time Teaching and Peer Instruction on the results of teaching a subject, of disciplinary character, in 17 students of a career on an initial teacher training belonging to Chile’s Council of Rectors. A pre and postest model was applied between August and December 2012. The analysis used descriptive techniques that allowed the characterization of the admission profile and inferentials to explain, statistically, the observed differences in the performance of the subjects. In terms of perception, a positive assessment of the relationship between students and the teacher in the classroom was observed, this stood out above the improvement in the handling of disciplinary content.